The legacies of two world wars : European societies in the twentieth century - Kettenacker, Lothar; Riotte, Torsten, 1972- (Berghahn Books, 2011)
"The US invasion of Iraq in 2003 was done mainly, if one is to believe US policy at the time, to liberate the people of Iraq from an oppressive dictator. However, the many protests in London, New York, and other cities imply that the policy of 'making the world safe for democracy' was not shared by millions of people in many western countries. Thinking about this controversy inspired the present volume, which takes a closer look at how society responded to the outbreaks and conclusions of the First and Second World Wars. In order to examine this relationship between the conduct of wars and public opinion, leading scholars trace the moods and attitudes of the people of four Western countries (Great Britain, France, Germany and Italy) before, during and after the crucial moments of the two major conflicts of the twentieth century. Focusing less on politics and more on how people experienced the wars, this volume shows how the distinction between enthusiasm for war and concern about its consequences is rarely clear-cut."--